Faktor Faktor yang Mempengaruhi Kinerja Karyawan pada Perusahaan Sinco Jaya Abadi - Silvia Sari Sitompul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
This study aims to examine the effect of Benefits, Incentives and Discipline on Employee Performance at company Sinco Jaya Abadi. The population in this research is all employees of company Sinco Jaya Abadi which amount 45 people. Since the total population is less than 100, the sampling technique used is censusor total sampling which using the entire population as sample. This research uses multiple linear regression method through statistical T test and model test F and Coefficient of determinant. The results showed that Allowance, Incentives and Discipline had partially significant influence on employee performance. From this research is expected that company can maintain and increase Allowance, Incentive and discipline so that employee performance of employees can increase. Keywords: Allowance, Incentives, Discipline, Employee Performance